2021
DOI: 10.1016/j.aap.2021.106299
|View full text |Cite
|
Sign up to set email alerts
|

The role of perceived legitimacy in understanding traffic rule compliance: A scoping review

Abstract: BackgroundPerceived legitimacy associated with rules and authorities is an important element for understanding and encouraging compliance with rules in the field of road safety, often more so than with a deterrence approach. Despite a growing interest in legitimacy in recent decades and in the psychological field in particular, its definitions and measurements appear to be heterogeneous, subject to debate and in need of a common theoretical framework. Therefore, one can expect these limitations to also concern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 67 publications
(151 reference statements)
0
46
0
3
Order By: Relevance
“…Perceived justice and the effectiveness of regulation measures on undesirable behaviors in society are related to the willingness to comply with the rules (Barkworth & Murphy, 2015;Bowers & Robinson, 2012). Therefore, it is expected that people will adhere more strictly to the traffic rules if they perceive the potential sanctions to be adequate and equal for every traffic user (Varet et al, 2021). The perceived legitimacy of safety regulations and sanctions has received increasing attention from scholars (Varet et al, 2021), but the effectiveness of traffic penalties remains an unresearched topic (Castillo-Manzano & Castro-Nuño, 2012;Castillo-Manzano et al, 2010;Du Plessis, Hartig, Jansen & Siebrits, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived justice and the effectiveness of regulation measures on undesirable behaviors in society are related to the willingness to comply with the rules (Barkworth & Murphy, 2015;Bowers & Robinson, 2012). Therefore, it is expected that people will adhere more strictly to the traffic rules if they perceive the potential sanctions to be adequate and equal for every traffic user (Varet et al, 2021). The perceived legitimacy of safety regulations and sanctions has received increasing attention from scholars (Varet et al, 2021), but the effectiveness of traffic penalties remains an unresearched topic (Castillo-Manzano & Castro-Nuño, 2012;Castillo-Manzano et al, 2010;Du Plessis, Hartig, Jansen & Siebrits, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is expected that people will adhere more strictly to the traffic rules if they perceive the potential sanctions to be adequate and equal for every traffic user (Varet et al, 2021). The perceived legitimacy of safety regulations and sanctions has received increasing attention from scholars (Varet et al, 2021), but the effectiveness of traffic penalties remains an unresearched topic (Castillo-Manzano & Castro-Nuño, 2012;Castillo-Manzano et al, 2010;Du Plessis, Hartig, Jansen & Siebrits, 2020). Deterrence theory deals with the perception of punishment, and assumes that traffic penalties should serve as deterrent when they have three characteristics: certainty, severity, and celerity of punishment (Nagin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Tyler et al (2015), perceived legitimacy was measured with a single-index scale mixing feeling of obligation to obey the police, moral alignment with the police, and moral alignment with the law. Varet et al (2021) argued that this point was problematic and that it would be preferable to focus on how best to define and measure the perceived legitimacy of a single object before investigating its possible generalization or adaptation to defining and measuring the perceived legitimacy of other objects. Subsequently, Varet et al (2021) focused their recommendations on defining the perceived legitimacy of traffic rules as this was the object most often considered in the studies they analyzed.…”
mentioning
confidence: 99%
“…Varet et al (2021) argued that this point was problematic and that it would be preferable to focus on how best to define and measure the perceived legitimacy of a single object before investigating its possible generalization or adaptation to defining and measuring the perceived legitimacy of other objects. Subsequently, Varet et al (2021) focused their recommendations on defining the perceived legitimacy of traffic rules as this was the object most often considered in the studies they analyzed. Importantly, they suggested that the perceived legitimacy of traffic rules could be articulated around a multidimensional model.…”
mentioning
confidence: 99%
See 1 more Smart Citation